THE EFFECT OF ACADEMIC MOTIVATION ON ACHIEVEMENT: A ROLE OF ACADEMIC ACTIVITY - Tatiana V. Semenova (Высшее образование в России)
The study focuses on the effect of academic motivation on achievement. Theoretical framework of the research is self-determination theory, which distinguishes several types of motivation and specifies relation between motivation and cognitive, behavioral outcomes. The database used in the study was collected in two waves of longitudinal project among undergraduate students enrolled in 2014 at six majors. Mediation analysis shows that academic motivation (general and situational) has indirect impact on achievement. Academic activity is mediator, which mediates effect of academic motivation on achievement. Students with more self-determined profile, who are engaged in learning activity for interest and pleasure, participate in active form of learning and get higher grade compared to students with less self-determined profile, who are guided by external stimuli.